James Dundas on John Cameron and Thomas Hobbes: Psychological Determinism and Compatibilism - Gellera, Giovanni (Reformation & Renaissance review, 2020)
The Idea philosophiae moralis (1679) by James Dundas (c.1620-1679) is an unfinished manuscript in the tradition of Reformed scholasticism. There Dundas answers the challenge posed by Thomas Hobbes’s professed proximity with Protestant theology on the issues of psychological determinism and the compatibilism of freedom and necessity in human agency. Dundas endorses the theology of conversion of the Scottish theologian John Cameron, discussed at the Synod of Dort (1618-1619) and taught in the Scottish universities until at least the 1630s. With the theological apparatus of Cameron, Dundas construes a version of intellectual determinism and compatibilism which seeks to preserve the role of divine predetermination, omnipotence and foreknowledge while rejecting Hobbes’s materialistic psychology and causality. This peculiar "dialogue" between Cameron and Hobbes also sheds new light on their reception in Scotland.